Chiral Bifunctional Thioureas and Squaramides Grafted into Old Polymers of Intrinsic Microporosity for Novel Applications - Valle, María (Polymers (Basel), 2018)
We have prepared different polymeric chiral bifunctional thioureas and squaramides by modification of the very well-known polymers of intrinsic microporosity (PIM), specifically PIM-1 and PIM-CO-1, to be used as recoverable organocatalysts. The installation of the chiral structures into the polymers has been done in two or three steps in high yields. The catalytic activity of the resulting materials has been proved in the stereoselective nitro-Michael addition and in a cascade process, which allows the synthesis of enantioenriched 4H-chromene derivatives. Squaramide II and thiourea III have been used in six cycles maintaining their activity.